Role of Brush Cytology in Diagnosis of Bronchial Carcinoma: Experience in Rajshahi Medical College Hospital - Islam, Md Rezaul; Sani, Ahmad Zainuddin; Majumdar, Samir C; Asafudullah, SM (TAJ: Journal of Teachers Association, 2020)
This was a descriptive study conducted in Rajshahi Medical College Hospital (RMCH), Rajshahi and the study period was from June 2017 to June 2019. A total number of 300 patients (48 females and 252 males) were enrolled who underwent elective fiber optic bronchoscopy with brush cytology for the diagnosis of bronchial carcinoma. Our aim was to identify the role of brush cytology in diagnosis of bronchial carcinoma. Most of the cases (84%) were male. Majority 111(37.00%) of the patients were in age group 60-72 years; the mean±SD age was (58.70±13.11). Most of the study participants were farmer 134(44.67%). 182(66.67%) were smoker and 118(39.33%) were non-smoker. For smokers, pack year history was <10 pack in 78(42.85%), 10-20 pack 66(36.26%) and >20 pack 38(20.87%) of cases. Squamous cell carcinoma was the most common type of bronchial carcinoma; found in 95 (31.66%) cases followed by adenocarcinoma 50 (16.66%), large cell carcinoma 43 (14.33%), small cell carcinoma 25 (8.33%), others 87 (29%) This study revealed that the bronchial brush cytology was minimally invasive, well enduring technique with high sensitivity in diagnosis of central lesion of bronchial carcinoma. TAJ 2019; 32(2): 1-6